Analysis of The Implementation of Halal Tourism Destination Development as an Effort to Improve The Economy of Banda Aceh City - Siregar, Muhammad Randha; Fuadi, Fuadi; Ichsan, Ichsan; Dharma, Yulius; Muhammad Nur, Mukhlis (Fakultas Syariah Institut Agama Islam Negeri Lhokseumawe, 2024)
The role of the Banda Aceh City government in increasing Halal Tourism Destination Development which is seen based on the number of visitors as the main benchmark in improving the economy of the community in this sector. There were 9 (nine) informants interviewed including the Banda Aceh City Tourism Office. This research was made to see from afar what are the shortcomings of the provision of halal tourism in Banda Aceh City. The research method used is qualitative by conducting interviews, as well as data reduction as the acquisition of research data. The results of the research obtained based on interviews with the Banda Aceh City Tourism Office, visitors, and traders are that the number of tourists coming to tourist destinations is increasing every year, except in 2020 due to Covid-19, most foreign visitors come from Malaysia, this is the application of regulations by the Banda Aceh City Tourism Office has improved, and the application of halal certification by business actors as one of the supporting indicators of Banda Aceh City Tourism.